Preface to the book This is life: the journey of uniportal VATS - Grodzki, Tomasz (Video-Assisted Thoracic Surgery; Vol 1 (September 2016): Video-Assisted Thoracic Surgery, 2016)
It is my great pleasure to recommend this important book written by well-known and widely respected authors, including my long-term friend Dr. Diego Gonzalez Rivas.